Reconstructing pre-Columbian agrarian territorialities in the El Alto-Ancasti mountain range, Eastern NW Argentina - Gastaldi, Marcos Román; Zuccarelli Freire, Verónica Natalia; Gheco, Lucas; Meléndez, Ana Soledad; Ferreyra, Sofía; Boscatto, Sofía; Egea, Débora; Rodríguez Oviedo, Melisa; Nagel, Antonela; Quesada, Marcos N.; Roberts, Patrick; Moreno, Enrique Alejandro (Frontiers in Environmental Archaeology, 2025)
In this paper, we examine the formation of a village landscape during the first millennium CE in the eastern Andes of South America, specifically in El Alto-Ancasti mountain range, Catamarca, Argentina. This landscape was shaped through the articulation of domestic spaces—houses located in elevated areas—productive areas—agricultural terraces in adjacent ravines—and ritual spaces—a distinctive form of rock art—that together reflect a deep understanding of and engagement with the local environment. In doing so, we critically assess previous archaeological and historical narratives that have portrayed these populations as marginal or peripheral to the cultural developments centered in the western valleys. As an alternative, we propose a theoretical and methodological approach grounded in local dynamics, with a particular focus on patterns of land use during this period. Furthermore, our analysis highlights both significant similarities in village landscapes across different ecological zones and important variations within them. These conclusions are supported by results from extensive interdisciplinary field and laboratory research.